DNMT1 reads heterochromatic H4K20me3 to reinforce LINE-1 DNA methylation - Wendan Ren (Nature Portfolio, 2021)
How histone modifications crosstalk with DNA methylation to regulate epigenomic patterning and genome stability in mammals remains elusive. Here, the authors show that DNA methyltransferase DNMT1 is a reader for histone H4K20 trimethylation via its BAH1 domain, which leads to optimal maintenance of DNA methylation at repetitive LINE-1 elements.